Solve for y (86y)/100+(87(100-83.1-y))/100=14.602

Math
86y100+87(100-83.1-y)100=14.602
Factor the equation.
Tap for more steps…
Combine the numerators over the common denominator.
86y+87(100-83.1-y)100=14.602
Rewrite 86y+87(100-83.1-y)100 in a factored form.
Tap for more steps…
Subtract 83.1 from 100.
86y+87(16.9-y)100=14.602
Apply the distributive property.
86y+87⋅16.9+87(-y)100=14.602
Multiply 87 by 16.9.
86y+1470.3+87(-y)100=14.602
Multiply -1 by 87.
86y+1470.3-87y100=14.602
Subtract 87y from 86y.
-y+1470.3100=14.602
Factor 0.1 out of -y+1470.3.
Tap for more steps…
Factor 0.1 out of -y.
0.1(-10y)+1470.3100=14.602
Factor 0.1 out of 1470.3.
0.1(-10y)+0.1(14703)100=14.602
Factor 0.1 out of 0.1(-10y)+0.1(14703).
0.1(-10y+14703)100=14.602
0.1(-10y+14703)100=14.602
0.1(-10y+14703)100=14.602
0.1(-10y+14703)100=14.602
Solve the equation.
Tap for more steps…
Multiply both sides of the equation by 100.
0.1(-10y+14703)=14.602⋅(100)
Simplify 0.1(-10y+14703).
Tap for more steps…
Apply the distributive property.
0.1(-10y)+0.1⋅14703=14.602⋅(100)
Simplify the expression.
Tap for more steps…
Multiply -10 by 0.1.
-1y+0.1⋅14703=14.602⋅(100)
Multiply 0.1 by 14703.
-1y+1470.3=14.602⋅(100)
Rewrite -1y as -y.
-y+1470.3=14.602⋅(100)
-y+1470.3=14.602⋅(100)
-y+1470.3=14.602⋅(100)
Multiply 14.602 by 100.
-y+1470.3=1460.2
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 1470.3 from both sides of the equation.
-y=1460.2-1470.3
Subtract 1470.3 from 1460.2.
-y=-10.1
-y=-10.1
Multiply each term in -y=-10.1 by -1
Tap for more steps…
Multiply each term in -y=-10.1 by -1.
(-y)⋅-1=(-10.1)⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=(-10.1)⋅-1
Multiply y by 1.
y=(-10.1)⋅-1
y=(-10.1)⋅-1
Multiply -10.1 by -1.
y=10.1
y=10.1
y=10.1
Solve for y (86y)/100+(87(100-83.1-y))/100=14.602
Scroll to top